GAGASAN NASIONALISME DAN WAWASAN KEBANGSAAN DALAM NOVEL INDONESIA MODERN - Wiyatmi Wiyatmi (Jurnal Penelitian Humaniora, 2002)
Abstract This study ia aimed at describing th idea of nationalism and the  concept of nation in modern Indonesian novels. The population is modern Indoneisan novels and the sampling of which is taken purposively and done through intensive reading. The analysis of the data covers 1)the structural aspect and 2) genetic aspects of the works. The first step analysis is meaning reconstruction and interpretation which are directed to  grasp the ideas and insight found in the linguistic expository involving  the ideas of nasionalism and the concept of nation. The second step anlysis concerns with the socio-cultural aspect overwhelming the writing of the works that is the self-existance of the writers and the ways they view their world. The findings show that in its historical perspective, the idea of nationalism have been categorized into three groups,namely: 1) the first wave nationalism; the idea of the pre-independence nationalism 2)the second-wave nationalism; the post independence nationalism, 3) the third-wave nationalism; the nationalism of the new Indonesia. Keywords: nationalism, modern Indonesian novels